2014
DOI: 10.1016/j.jcf.2013.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-specific alterations in vascular smooth muscle cell function in cystic fibrosis piglets

Abstract: BACKGROUND The most common CF-causing mutations interfere with CFTR trafficking from the endoplasmic reticulum (CFTR-F508del) or prematurely terminate transcription (CFTR-null). We suspected genotype-specific pattens of CFTR expression would have differential effects on smooth muscle cell calcium signaling and hence vascular tone. We hypothesized that compared to wild-type or CFTR-null aorta, aorta from CFTR-F508del (dF) piglets will have reduced endoplasmic reticulum calcium mobilization and decreased vasocon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…First, CFTR channels exist on human lung microvascular cells 27 and directly cause pulmonary vascular relaxation through CFTR channel activation 28 , 29 . Additionally, CFTR mediates vascular tone independent from its role as a chloride channel through other mechanisms including stimulating nitric oxide generation via ATP release 30 , altering lipid trafficking and vascular smooth muscle cell calcium handling 31 , 32 , and through increasing expression of vascular growth factors, including VEGF-A 33 . In addition, CFTR SNPs have previously been associated with altered flow mediated dilation and flow velocity in humans 34 .…”
Section: Discussionmentioning
confidence: 99%
“…First, CFTR channels exist on human lung microvascular cells 27 and directly cause pulmonary vascular relaxation through CFTR channel activation 28 , 29 . Additionally, CFTR mediates vascular tone independent from its role as a chloride channel through other mechanisms including stimulating nitric oxide generation via ATP release 30 , altering lipid trafficking and vascular smooth muscle cell calcium handling 31 , 32 , and through increasing expression of vascular growth factors, including VEGF-A 33 . In addition, CFTR SNPs have previously been associated with altered flow mediated dilation and flow velocity in humans 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Robert et al reported the expression of CFTR in PASMCs and demonstrated its involvement in the modulation of pulmonary arterial tone (14). In the systemic circulation, CFTR-F508del, the most common mutation underlying human CF disease, has recently been associated with diminished Ca 2+ release in vascular smooth muscle cells, decreased aortic tone, and responsiveness (15). Of specific relevance for HPV, CFTR was recently shown to directly interact with TRPC6, thus regulating TRPC6-dependent Ca 2+ influx (16).…”
Section: Significancementioning
confidence: 99%
“…[7] Although the pathophysiological implications of ATP2B1 gene on the development of hypertension are still unclear, results from ATP2B1 knockout mouse studies suggested that ATP2B1 may play an important role in the regulation of blood pressure[8] through alterations of calcium handling and vasoconstriction in vascular smooth muscle cells. [9]…”
Section: Introductionmentioning
confidence: 99%